Ultrafast and scalable microwave-assisted synthesis of activated hierarchical porous carbon for high-performance supercapacitor electrodes - Seong, Kwang dong; Jin, Xuanzhen; Kim, Deokhwan; Kim, Jong Min; Ko, Dongjin; Cho, Youngseul; Hwang, Minsik; Kim, Ju Hyung; Piao, Yuanzhe (Journal of Electroanalytical Chemistry, 2020)
The fabrication of activated hierarchical porous carbon materials normally requires multiple processing steps involving pyrolysis and activation with long reaction times under controlled gas conditions. This article presents an ultrafast and scalable synthesis of hierarchical porous activated carbon via one-step microwave heating, using a homogeneous mixture of potassium citrate and carbon black. For this work, the mixture was simply covered with a glass chamber to accompany spontaneous changes in environmental conditions from air to CO/CO2 gases. Under microwave irradiation, simultaneous carbonization and activation processes were completed within a very short period of time, resulting in the formation of hierarchical porous carbon with a high specific surface area of 1280.4 m2 g−1. When the prepared porous carbon was used as an electrode material for electric double-layer capacitors, it exhibited a remarkable specific capacitance of 318 F g−1 at a current density of 1 A g−1 in a three-electrode system. In addition, the electric double-layer capacitor using the optimized porous carbon showed a high energy density of 0.55 mWh cm−3 with a power density of 12.92 mW cm−3, as well as excellent long-term cycle stability in a symmetric two-electrode configuration.
Keywords: Environmental conditions; Hierarchical porous carbons; High energy densities; High specific surface area; Microwave assisted synthesis; Specific capacitance; Supercapacitor electrodes; Three electrode-system; Carbon black; Electric double-layer capacitors; Hierarchical porous carbon; Microwave irradiation; Potassium citrate